Silicon monoxide composite powder, preparation method thereof and lithium battery negative electrode
Patent Information
- Application Number
- CN202610832348.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-30
AI Technical Summary
例如,本发明的目的之一在于提供一种氧化亚硅复合粉体制备方法,该方法通过分子级设计,在氧化亚硅颗粒表面自内向外依次构建硅氧无机锚定层、富氢键有机-无机互穿软相层和含氟有机调控层,形成力学性能由高到低递变、化学组成由无机组分向有机组分梯度过渡的有序异质结构,解决现有技术中氧化亚硅在水系加工体系下分散性差、界面相容性不足以及后续界面稳定性不理想的问题
[0016]与现有技术相比,本发明的有益效果至少包含以下中的至少一项:
Smart Images

Figure CN123017911A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery electrode materials, and more specifically, relates to a silicon suboxide composite powder and its preparation method, and a lithium battery anode. Background Technology
[0002] Silicon suboxide (SiO2) has become a key candidate for high-energy-density anode materials in lithium-ion batteries due to its combination of high specific capacity and relatively superior structural stability compared to pure silicon. However, in practical applications, SiO2 still suffers from problems such as high surface activity, significant interfacial side reactions, large initial irreversible capacity, and limited cycle stability. Meanwhile, as electrode manufacturing processes move towards greener and lower-cost approaches, aqueous anode processing is gaining increasing attention. However, SiO2 particles in aqueous environments are prone to uneven dispersion, increased agglomeration, and insufficient interfacial compatibility with aqueous binders, which in turn affects slurry stability, electrode film quality, and final electrochemical performance.
[0003] In existing technologies, fluoropolymers are typically used as binders or additives, or silane coupling agents are used to treat the particle surface to improve interfacial stability or enhance the compatibility of the material with organic systems. However, these methods mostly involve single-component modification or simple physical introduction, making it difficult to form a structured functional layer on the surface of silicon suboxide particles that simultaneously provides stable anchoring and outer-layer interfacial regulation. Especially in aqueous anode processing systems, traditional single-layer modification struggles to simultaneously regulate multiple interfacial behaviors between particles and the liquid phase, particles and binders, and particles themselves, thus failing to meet the comprehensive requirements of silicon suboxide materials in aqueous processing and subsequent electrochemical applications.
[0004] Therefore, it is necessary to develop a new method for constructing silicon suboxide surfaces to improve the interfacial compatibility of silicon suboxide in aqueous anode processing and enhance its performance in lithium-ion batteries. Summary of the Invention
[0005] To address the shortcomings of existing technologies, one objective of this invention is to solve one or more problems existing in the prior art. For example, one objective of this invention is to provide a method for preparing silica suboxide composite powder. This method, through molecular-level design, sequentially constructs a silicon-oxygen inorganic anchoring layer, a hydrogen-rich organic-inorganic interpenetrating soft phase layer, and a fluorine-containing organic regulating layer on the surface of silica suboxide particles from the inside out. This forms an ordered heterogeneous structure with mechanical properties gradually decreasing from high to low and a chemical composition gradually transitioning from inorganic to organic components. This solves the problems of poor dispersibility, insufficient interfacial compatibility, and unsatisfactory subsequent interfacial stability of silica suboxide in aqueous processing systems in existing technologies.
[0006] One aspect of the present invention provides a method for preparing silica-suboxide composite powder, which may include the following steps: mixing a first silicon source and a second silicon source in an organic solvent, adjusting the amount of water added and the temperature to control the degree of hydrolysis, to obtain an active precursor sol, wherein the first silicon source is a fluorinated silane or a fluorinated siloxane oligomer, and the second silicon source is a non-fluorinated silane or a silicate ester; mixing silica-suboxide powder with the active precursor sol to form a silicon-oxygen inorganic anchoring layer on the surface of the silica-suboxide powder; adding an activator containing polar hydrogen donor functional groups to form a hydrogen-rich organic-inorganic interpenetrating soft phase layer interpenetrating with the silicon-oxygen inorganic anchoring layer through hydrogen bonding and coordination; adding a fluorinated organic precursor and a crosslinking aid to form a fluorinated organic regulating layer on the surface of the hydrogen-rich organic-inorganic interpenetrating soft phase layer; and performing solid-liquid separation, washing, and curing treatment to obtain silica-suboxide composite powder with a gradient fluorinated hybrid precursor layer on the surface.
[0007] Furthermore, the active precursor sol can be an active precursor sol containing 30% to 70% alkoxy groups that have not been hydrolyzed.
[0008] Furthermore, adjusting the amount of water added and controlling the degree of hydrolysis by temperature control can include controlling the molar ratio of water added to the total of the first and second silicon sources to be (0.1~10):1, and the temperature to be 0~60℃; the molar ratio of the first silicon source to the second silicon source can be (0.05~20):1.
[0009] Furthermore, the fluorinated organic precursor may be selected from one or more of fluorinated polyurethane, fluorinated polyimide, fluorinated acrylate polymer and fluorinated oligomer; the crosslinking aid may be selected from one or more of polyisocyanate blocking agents, dialdehyde compounds and hydrolyzable silane coupling agents.
[0010] Furthermore, the fluorinated organic control layer can be selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride copolymers, fluorinated acrylate polymers, fluorinated polyimides, fluorinated rubbers, fluorinated surfactants, and fluorinated oligomers.
[0011] Furthermore, the curing process may include placing the washed material in a mixed atmosphere of water vapor and alcohol vapor and performing steam-induced curing at 50°C to 150°C.
[0012] Furthermore, the curing process may include placing the washed material in an atmosphere containing alcohol vapor and treating it at 60°C to 100°C for 0.5h to 2h, and then placing it in a mixed atmosphere containing water vapor and alcohol vapor and treating it at 50°C to 150°C for 1h to 4h.
[0013] In another aspect, the present invention provides a silicon suboxide composite powder, which can be prepared by the silicon suboxide composite powder preparation method described above, wherein the thickness of the silicon-oxygen inorganic anchoring layer can be 2 nm to 10 nm, the thickness of the hydrogen-rich organic-inorganic interpenetrating soft phase layer can be 1 nm to 5 nm, and the thickness of the fluorine-containing organic regulating layer can be 5 nm to 20 nm.
[0014] In another aspect, the present invention provides a lithium battery anode that may contain the silicon suboxide composite powder as described above.
[0015] In another aspect, the present invention provides a lithium battery that may include the lithium battery negative electrode as described above.
[0016] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:
[0017] (1) The method of the present invention sequentially constructs a Si–O–Si highly cross-linked silicon-oxygen inorganic anchoring layer, a hydrogen-rich organic-inorganic interpenetrating soft phase layer, and a fluorinated organic regulating layer on the surface of silicon suboxide particles. The relative content of the Si–O–Si structure decreases from the inner layer to the outer layer, while the relative content of the fluorinated organic groups increases from the inner layer to the outer layer, forming a gradient structure with decreasing rigidity and increasing flexibility from the inside to the outside. The gradient structure is beneficial to balance the bonding stability of the silicon suboxide surface and the interface regulation capability of the outer layer. The low-modulus fluorinated segments in the outer layer generate steric hindrance through dynamic conformational inversion in the aqueous medium, effectively blocking direct hydrogen bond aggregation between particles. This completely solves the problem of severe aggregation of aqueous slurries caused by the high surface energy of traditional inorganic fluorinated layers (such as LiF), enabling highly electrochemical functional particles to have excellent aqueous dispersion stability for the first time.
[0018] (2) The method of this invention introduces an anchoring activator containing multiple functional groups to introduce a "hydrogen-rich interpenetrating soft phase" into a rigid inorganic network. It utilizes strong hydrogen bond networks such as F···H2O to construct low-impedance ion conduction channels similar to a liquid environment, significantly improving the intrinsic ionic conductivity of the hybrid interface layer. This mechanism is fully compatible with aqueous preparation environments, unlike traditional doping or coating methods, and effectively solves the defects of conventional coating layers in terms of ion insulation.
[0019] (3) The outermost exposed free polar functional groups of the gradient-type fluorinated hybrid precursor layer of the present invention achieve a dual response in aqueous slurry preparation: firstly, the steric hindrance of the outer fluorinated chain segments prevents particle agglomeration; secondly, it forms a reversible hydrogen bond or coordination bond network with the molecular chains of waterborne binders (PAA, CMC, etc.), so that the silica-suboxide composite powder is uniformly anchored in the binder matrix as a "crosslinking node", forming a hydrodynamic bridge. This mechanism greatly improves the stability of the slurry and the uniformity of electrode coating.
[0020] (4) During the initial lithium intercalation process, the outer fluorine-containing organic control layer of the composite powder prepared in this invention undergoes in-situ defluorination and reconstruction, inducing the inorganic lithium salt (such as LiF) generated by electrolyte decomposition to be deposited in a confined manner along the underlying organic network, ultimately evolving into a dense and flexible organic-inorganic interpenetrating composite SEI film. This film fundamentally suppresses the continuous side reactions between silicon suboxide and the electrolyte, significantly improving the initial coulombic efficiency and long-term cycle stability, making it suitable for high-energy-density lithium-ion batteries. Attached Figure Description
[0021] The above and other objects and features of the present invention will become clearer from the following description taken in conjunction with the accompanying drawings, in which:
[0022] Figure 1 The XPS spectrum of the negative electrode F1s prepared in Example 1.
[0023] Figure 2 This is a comparison chart of the specific capacity of Example 1 and Comparative Example 1 after 200 cycles. Detailed Implementation
[0024] The following description, in conjunction with the accompanying drawings and exemplary embodiments, details the silicon suboxide powder and its preparation method, as well as the lithium battery anode, according to the present invention.
[0025] This invention provides a method for preparing silica-suboxide composite powder. In some embodiments, the preparation method includes the following steps:
[0026] Step S01: Synthesize the active precursor sol. A first silicon source and a second silicon source are mixed in an organic solvent. The amount of water added and the temperature are adjusted to control the degree of hydrolysis, resulting in the active precursor sol. The first silicon source is a fluorinated silane or a fluorinated siloxane oligomer, and the second silicon source is a non-fluorinated silane or a silicate ester.
[0027] Step S02: Constructing a silicon-oxygen inorganic anchoring layer. Silicon suboxide powder is mixed with an active precursor sol to form a silicon-oxygen inorganic anchoring layer on the surface of the silicon suboxide powder.
[0028] Step S03: Construct a hydrogen-rich organic-inorganic interpenetrating soft phase layer. An activator containing polar hydrogen donor functional groups is added, and hydrogen-rich organic-inorganic interpenetrating soft phase layers are formed on the surface of the silicon-oxygen inorganic anchoring layer through hydrogen bonding and coordination interactions.
[0029] Step S04: Assemble the outer fluorinated organic control layer. A fluorinated organic precursor and a crosslinking aid are added to form the fluorinated organic control layer on the surface of the hydrogen-rich organic-inorganic interpenetrating soft phase layer.
[0030] Step S05: Solid-liquid separation, washing, and curing treatment to obtain silica-suboxide composite powder with a gradient fluorine-containing hybrid precursor layer on the surface.
[0031] In some embodiments, the preparation method may further include a drying pretreatment of the silica powder before mixing it with the active precursor sol. This drying pretreatment removes physically adsorbed water and impurities from the powder surface, while simultaneously exposing the silanol groups (Si-OH) and oxygen bridging defect sites on the powder surface, providing sufficient active reaction sites for the subsequent chemical anchoring of the active precursor sol. For example, the drying pretreatment may include drying at 100°C to 140°C for 6 to 10 hours. Another example is drying at 120°C for 8 hours.
[0032] In some embodiments, the organic solvent in step S01 can be a mixed solvent of anhydrous ethanol and isopropanol. For example, it can be a mixed solvent formed by anhydrous ethanol and isopropanol in a volume ratio of 3:1. By mixing the first silicon source and the second silicon source in a certain proportion, adding a hydrolysis catalyst (e.g., glacial acetic acid or dilute hydrochloric acid to adjust the pH of the system to 4-5), and controlling the amount of water added and the temperature, the homogeneous self-polymerization of the silicon source in the solution is suppressed, causing the first silicon source and the second silicon source to undergo partial hydrolysis and pre-condensation reactions, obtaining an active precursor sol that retains 30% to 70% of unhydrolyzed alkoxy groups, creating conditions for subsequent directional heterogeneous condensation on the silicon suboxide surface. For example, the active precursor sol retains 35%, 40%, 46%, 55%, 67% of unhydrolyzed alkoxy groups.
[0033] In some implementations, the molar ratio of water to the total of the first and second silicon sources can be (0.1~10):1. For example, the molar ratio of water to the total of the first and second silicon sources can be a combination of (0.3~9.5):1, (1.8~8.2):1, (3.2~6.9):1, (4.3~5.5):1, or higher. The hydrolysis temperature can be 0~60℃. For example, the hydrolysis temperature can be a combination of 8℃~55℃, 15℃~50℃, 23℃~43℃, 30℃~38℃, or higher. The hydrolysis time can be adjusted according to the degree of hydrolysis. For example, the hydrolysis time can be 4 min~8 min. Another example is a hydrolysis time of 5 min. The molar ratio of the first silicon source to the second silicon source can be (0.05~20):1. For example, the molar ratio of the first silicon source to the second silicon source can be a combination of (0.1~18):1, (0.5~20):1, (1.5~15):1, (2~12):1, (5~9):1 or more.
[0034] In some embodiments, the first silicon source can be a fluorinated silane coupling agent. For example, the first silicon source can be 1H,1H,2H,2H-perfluorooctyltriethoxysilane or fluoroalkyltrialkoxysilane. The second silicon source can be tetraethyl orthosilicate or methyltriethoxysilane, etc.
[0035] In some implementations, for step S02, silica suboxide powder is dispersed in an active precursor sol. The abundant silanol groups on the silica suboxide surface undergo a co-condensation reaction with the reactive alkoxy groups in the active precursor, causing an in-situ co-condensation deposition of the silica-oxygen network on the powder particle surface, forming a highly cross-linked silica-oxygen inorganic anchoring layer that is tightly bonded to the matrix. This layer, as the constructed inner anchoring layer, primarily plays a role in strong interfacial bonding.
[0036] In some implementations, for step S03, an anchoring surfactant containing multiple polar hydrogen donor functional groups is introduced into the reaction system of step S02. Utilizing its small molecule properties, it penetrates into the not-yet-fully-cured silicon-oxygen inorganic anchoring layer. The polar hydrogens (-OH, -NH2, etc.) on the activator form strong hydrogen bonds (F···HO or O···HN, etc.) with fluorine atoms or bridging oxygen atoms in the silicon-oxygen inorganic anchoring layer. Through hydrogen bonding and coordination, a flexible, hydrogen-bonded organic-inorganic interpenetrating soft phase layer is constructed in situ within the rigid silicon-oxygen inorganic anchoring layer. This layer can serve as a "liquid-like" channel for rapid ion conduction, located outside and interspersed within the silicon-oxygen inorganic anchoring layer. The anchoring surfactant (an activator containing polar hydrogen donor functional groups) can be a polyphenol or polyamine compound. For example, the anchoring surfactant can be one or more of tannic acid, gallic acid, dopamine hydrochloride, catechol and polyethyleneimine.
[0037] In some embodiments, for step S04, a fluorinated organic precursor containing reactive end groups and a corresponding crosslinking aid are added to the system constructed with the inner layer (silicon-oxygen inorganic anchoring layer) and the intermediate layer (hydrogen-rich organic-inorganic interpenetrating soft phase layer). These components preferentially bind to the outer side of the hydrogen-rich organic-inorganic interpenetrating soft phase layer formed in step S03, forming a continuous, flexible outer fluorinated organic network through chemical bonding, hydrogen bonding, or entanglement. In some embodiments, the fluorinated organic precursor may be selected from one or more of fluorinated polyurethanes, fluorinated polyimides, fluorinated acrylate polymers, and fluorinated oligomers. The fluorinated organic precursor contains reactive end groups; without reactive end groups, in-situ SEI reconstruction cannot be induced. For example, the fluorinated organic precursor can be one or more of the following: fluorinated polyurethane prepolymer (fluorine content 10-30 wt%, NCO content 3-8%), fluorinated acrylate copolymer (fluorine content 15-40 wt%), fluorinated polyimide precursor (fluorine content 20-35 wt%), PVDF-HFP copolymer (HFP content 5-15%), and perfluorinated polyether glycol (molecular weight approximately 1000-4000). The crosslinking aid can be selected from one or more of the following: blocked polyisocyanates, dialdehyde compounds, and hydrolyzable silane coupling agents. For example, the crosslinking aid can be one or more of the following: blocked polyisocyanates (unblocking temperature 80-120℃), glutaraldehyde aqueous solution (concentration 25%), and hydrolyzable silane coupling agents (KH-550 / KH-560).
[0038] In some embodiments, for step S05, after solid-liquid separation and washing of the product obtained in step S04, it can be placed in a mixed atmosphere containing water vapor and alcohol vapor for steam-induced curing. The curing temperature can be 50℃~150℃, and the curing time can be 1h~4h. At these curing temperatures and times, premature cross-linking of the organic layer can be avoided, ensuring gradual densification of the inorganic network and facilitating the formation of a gradient structure. For example, the curing temperature can be a combination of 55℃~140℃, 72℃~128℃, 89℃~112℃, 95℃~107℃, or higher, and the curing time can be 2h~3h. Preferably, the curing process can first be carried out in an atmosphere containing alcohol vapor at 60℃~100℃ for 0.5h~2h, and then in a mixed atmosphere containing water vapor and alcohol vapor at 50℃~150℃ for 1h~4h. This two-step curing method achieves the most thorough interfacial molecular-level interlocking and optimal gradient synergy, resulting in better chemical properties of the composite powder. In the aforementioned mixed atmosphere, the partial pressure of water vapor can be 30-70 vol%. During the curing process, alcohol vapor promotes the deep alcoholysis condensation of alkoxy groups remaining in the inner layer (silicon-oxygen inorganic anchoring layer) from step S02, further densifying the inorganic network. Water vapor, on the other hand, triggers the hydrolysis and crosslinking reaction of the outer layer crosslinking aid, curing the fluorinated organic network (fluorinated organic regulatory layer). This process achieves molecular-level chemical interlocking between the inorganic and organic networks at the interface, ultimately forming an ordered gradient fluorinated heterogeneous interface layer on the silicon suboxide surface with decreasing crosslinking density and Young's modulus from the inside out. The formed gradient fluorinated hybrid precursor layer can be further transformed into a surface-derived layer containing both silicon-oxygen network and fluorinated interface components during subsequent aqueous anode processing and the first electrochemical process, improving the performance of the composite material in battery applications.
[0039] In some embodiments, the fluorinated organic control layer may be selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride copolymers, fluorinated acrylate polymers, fluorinated polyimides, fluorinated rubbers, fluorinated surfactants, and fluorinated oligomers. The fluorinated organic control layer can be used to further control the interfacial behavior of silica particles in an aqueous processing environment.
[0040] In another aspect, this invention provides a silicon suboxide composite powder. In some embodiments, the composite powder comprises silicon suboxide and a gradient-type fluorine-containing hybrid precursor layer coated on the surface of the silicon suboxide. The gradient-type fluorine-containing hybrid precursor layer includes, from the inside out, a silicon-oxygen inorganic anchoring layer on the surface of the silicon suboxide, a hydrogen-rich organic-inorganic interpenetrating soft phase layer interpenetrating and bonded to the outside of the silicon-oxygen inorganic anchoring layer, and an outermost fluorine-containing organic regulating layer. In some embodiments, the thickness of the silicon-oxygen inorganic anchoring layer can be 2 nm to 10 nm, the thickness of the hydrogen-rich organic-inorganic interpenetrating soft phase layer can be 1 nm to 5 nm, and the thickness of the fluorine-containing organic regulating layer can be 5 nm to 20 nm. The thicknesses of the layers described above can achieve synergistic optimization of mechanical and chemical gradients, taking into account structural stability, ion conduction, and interface compatibility. For example, the thickness of the silicon-oxygen inorganic anchoring layer can be 3 nm to 8 nm, the thickness of the hydrogen-rich organic-inorganic interpenetrating soft phase layer can be 2 nm to 4 nm, and the thickness of the fluorine-containing organic regulating layer can be 7 nm to 16 nm. For example, the thickness of the silicon-oxygen inorganic anchoring layer can be 4nm to 6nm, the thickness of the hydrogen-rich organic-inorganic interpenetrating soft phase layer can be 2.8nm to 3nm, and the thickness of the fluorine-containing organic control layer can be 10nm to 13nm.
[0041] In another aspect, the present invention provides a lithium battery anode that may contain the silicon suboxide composite powder as described above.
[0042] In some implementations, the prepared silicon suboxide composite powder can also be carbon-coated as a lithium battery anode material. For example, carbon coating can be performed by CVD at 650℃~950℃ for 0.5h~5h, with the carbon source being an acetylene / methane mixture. The thickness of the carbon coating can be controlled to be 2nm~8nm. As another example, a carbon layer of 3nm~7nm can be coated at 700℃~900℃.
[0043] In another aspect, the present invention provides a lithium battery that may include the lithium battery negative electrode as described above.
[0044] To better understand the present invention, specific examples are provided below to further illustrate the content of the present invention, but the content of the present invention is not limited to the examples below.
[0045] Example 1
[0046] A method for preparing silica-suboxide composite powder may include the following steps:
[0047] Step 1: Place the silica powder (average particle size D50 of 5.0 μm, purity ≥99.5%) at 120℃ and vacuum dry for 8 hours to remove surface physically adsorbed water and expose active sites.
[0048] Step 2: 1H,1H,2H,2H-perfluorooctyltriethoxysilane (FOTS, primary silicon source, purity ≥97%) and tetraethyl orthosilicate (TEOS, secondary silicon source, purity ≥99%) were added to a mixed solvent of anhydrous ethanol and isopropanol (volume ratio 3:1, water content <500 ppm). Glacial acetic acid was added as a hydrolysis catalyst, and deionized water was added. The molar ratio of 1H,1H,2H,2H-perfluorooctyltriethoxysilane to tetraethyl orthosilicate was controlled at 1:4, and the molar ratio of deionized water to total silicon source was controlled at 2:1. The hydrolysis condensation temperature was 30℃, and the hydrolysis was carried out for 5 min. About 50% of the unhydrolyzed alkoxy groups were retained to obtain the active precursor sol.
[0049] Step 3: Add the silica powder obtained in Step 1 to the active precursor sol, and in-situ co-condensation deposition occurs on the surface of the silica particles to form a highly cross-linked silicon-oxygen inorganic anchoring layer, which serves as the inner anchoring layer.
[0050] Step 4: Add tannic acid as an activator to the system obtained in Step 3 to form a hydrogen-rich organic-inorganic interpenetrating soft phase layer through hydrogen bonding and coordination.
[0051] Step 5: Add a fluorinated polyurethane prepolymer as a fluorinated organic precursor and a blocked polyisocyanate as a crosslinking aid to the system in step 4. After the reaction is completed, a fluorinated organic control layer is formed on the surface of the hydrogen-rich organic-inorganic interpenetrating soft phase layer.
[0052] Step 6: Solid-liquid separation, washing, and curing treatment in a mixed atmosphere of water vapor and ethanol vapor (water vapor partial pressure ratio 40 vol%), with a curing temperature of 80℃ and a treatment time of 2h, to obtain silicon suboxide composite powder with a gradient fluorine-containing hybrid precursor layer on the surface.
[0053] Figure 1 The figure shows the F 1s spectrum of the negative electrode prepared in this embodiment. As can be seen from the figure, a distinct characteristic peak appears at approximately 688.6 eV, which is attributed to the C–F / CF2 / CF3 bonds in the FOTS perfluoroalkyl chain and the outer layer of fluorinated polyurethane. After the first lithium insertion, the LiF characteristic peak at approximately 685.0 eV is significantly enhanced, while the high binding energy C–F peak is relatively weakened, indicating that the outer fluorinated organic control layer undergoes partial defluorination and reconstruction, inducing the formation of a LiF-rich composite SEI.
[0054] Example 2
[0055] Compared with Example 1, this example controls the molar ratio of the first silicon source to the second silicon source to be 1:10, the water / total silicon molar ratio to be 3:1, the hydrolysis temperature to be 20°C, retains about 60% of unhydrolyzed alkoxy groups, uses gallic acid as the activator, uses fluorinated organic precursor as fluorinated acrylate copolymer, uses glutaraldehyde as crosslinking aid, and uses 100°C as curing temperature. Other aspects are the same as in Example 1.
[0056] Example 3
[0057] Compared to Example 1, this example controls the molar ratio of the first silicon source to the second silicon source to be 1:1, the water / total silicon molar ratio to be 5:1, the hydrolysis temperature to be 40°C, and retains approximately 40% of unhydrolyzed alkoxy groups. The activator is dopamine. The fluorinated organic precursor is a fluorinated polyimide precursor, and the curing temperature is 120°C; all other aspects are the same as in Example 1.
[0058] Example 4
[0059] Compared to Example 1, this example controls the first silicon source to be a fluorinated siloxane oligomer, the second silicon source to be methyltriethoxysilane, the molar ratio of the first to the second silicon source to be 3:1, the water / total silicon molar ratio to be 2.5:1, the hydrolysis temperature to be 10°C, and retains approximately 65% of unhydrolyzed alkoxy groups. The activator is catechol. The fluorinated organic precursor is a PVDF-HFP copolymer, and the crosslinking aid is the silane coupling agent KH-560. The curing temperature is 90°C, and other aspects are the same as in Example 1.
[0060] Example 5
[0061] Compared to Example 1, this example controls the molar ratio of the first silicon source to the second silicon source to be 1:20, the water / total silicon molar ratio to be 0.5:1, the hydrolysis temperature to be 0°C, and retains approximately 70% of unhydrolyzed alkoxy groups. The activator is tea polyphenols. The fluorinated organic precursor is fluorinated polyurethane, and the crosslinking aid is a dialdehyde. The curing temperature is 150°C, and the alcohol / water mixed vapor treatment lasts for 4 hours; all other aspects are the same as in Example 1.
[0062] Example 6
[0063] Compared with Example 1, the crosslinking aid in this example is a hydrolyzable silane coupling agent (KH-550), the curing temperature is 100℃, and the rest is the same as in Example 1.
[0064] Example 7
[0065] Compared with Example 2, the activator in this example is changed to polyethyleneimine, the water / total silicon molar ratio is 4:1, the hydrolysis temperature is 25°C, and the rest is the same as in Example 2.
[0066] Example 8
[0067] Compared with Example 1, the fluorinated organic precursor in this example uses a fluorinated oligomer (perfluoropolyether glycol), the crosslinking agent is a blocked isocyanate, and the curing temperature is 110°C.
[0068] Example 9
[0069] Compared with Example 1, this example uses a two-step curing process: first, alcohol vapor treatment at 80°C for 1 hour, and then alcohol / water mixed vapor treatment at 120°C for 2 hours.
[0070] Comparative Example 1
[0071] This comparative example uses only non-fluorinated silanes (TEOS) to construct a single silicon-oxygen layer, without an intermediate soft phase layer or an outer fluorinated organic layer. The specific preparation method includes:
[0072] Step 1: Place the silica powder (average particle size D50 of 5.0 μm, purity ≥99.5%) in a vacuum dryer at 120℃ for 8 h to remove surface physically adsorbed water and expose active sites.
[0073] Step 2: Add tetraethyl orthosilicate (TEOS, purity ≥99%) to a mixed solvent of anhydrous ethanol and isopropanol (volume ratio 3:1, water content <500 ppm), add glacial acetic acid as a hydrolysis catalyst, and add deionized water to control the molar ratio of water to TEOS to be 2:1. The hydrolysis condensation temperature is 30℃, and the hydrolysis is carried out for 5 min to obtain a non-fluorosilane hydrolyzed sol.
[0074] Step 3: Add the silica powder obtained in Step 1 to the above sol and stir for 2 hours to allow TEOS to undergo in-situ hydrolysis and condensation on the surface of silica particles, forming a single silicon-oxygen inorganic layer.
[0075] Step 4: Solid-liquid separation, washing three times with anhydrous ethanol, and vacuum drying at 80°C for 2 h to obtain silicon suboxide powder with only a non-fluorinated silicon oxide layer on the surface.
[0076] Comparative Example 2
[0077] This comparative example uses only a one-step coating method with fluorinated silanes, without an inner-outer layer gradient structure. Specific preparation methods include:
[0078] Step 1: Place the silica powder (average particle size D50 of 5.0 μm, purity ≥99.5%) in a vacuum dryer at 120℃ for 8 h to remove surface physically adsorbed water and expose active sites.
[0079] Step 2: Add 1H,1H,2H,2H-perfluorooctyltriethoxysilane (FOTS) to a mixed solvent of anhydrous ethanol and isopropanol (volume ratio 3:1, water content <500 ppm), add glacial acetic acid as a hydrolysis catalyst, and add deionized water to control the water to FOTS molar ratio to 2:1. The hydrolysis condensation temperature is 30℃, and the hydrolysis is carried out for 5 min to obtain a fluorinated silane hydrolysate.
[0080] Step 3: Add the silica powder obtained in Step 1 to the above sol and stir for 2 hours to allow the fluorinated silane to undergo hydrolysis and condensation on the particle surface to form a single-layer fluorinated coating.
[0081] Step 4: Solid-liquid separation, washing three times with anhydrous ethanol, and vacuum drying at 80°C for 2 h to obtain silica powder with only a single layer of fluorinated silane coating on the surface.
[0082] Comparative Example 3
[0083] Compared with Example 1, this comparative example omits step 4, i.e., after forming the highly cross-linked silicon-oxygen inorganic anchoring layer in step 3, the fluorine-containing organic precursor and cross-linking aid are directly added, and no hydrogen-rich organic-inorganic interpenetrating soft phase layer is formed.
[0084] Comparative Example 4
[0085] This comparative example involves a simple blending of silica and PVDF to prepare a slurry, without chemical anchoring. The specific preparation process includes:
[0086] Step 1: Place the silica powder (average particle size D50 of 5.0 μm, purity ≥99.5%) in a vacuum dryer at 120℃ for 8 h.
[0087] Step 2: Mix the dried silica powder with polyvinylidene fluoride (PVDF, molecular weight approximately 500,000) at a mass ratio of 8:2, add N-methylpyrrolidone (NMP) as a solvent, and mechanically stir at room temperature for 2 hours to form a uniform slurry.
[0088] Step 3: The above slurry was vacuum dried at 80°C for 12 h to remove NMP and obtain a blocky composite.
[0089] Step 4: Grind the blocky composite and pass it through a 200-mesh sieve to obtain a physically blended composite powder of silica and PVDF. This powder has no chemically bonded gradient coating layer.
[0090] Comparative Example 5
[0091] This comparative example demonstrates the formation of a LiF layer on a silicon suboxide surface via vapor-phase fluorination. The specific preparation process includes:
[0092] Step 1: Place the silica powder (average particle size D50 of 5.0 μm, purity ≥99.5%) in a vacuum dryer at 120℃ for 8 h.
[0093] Step 2: Load the dried silica powder into a quartz boat, place it in a tube furnace, purge the air with argon gas, and then switch to a F2 / N2 mixture with a volume ratio of 1:9 and a total gas flow rate of 100 mL / min.
[0094] Step 3: Increase the temperature to 300℃ at a rate of 5℃ / min and maintain this temperature for 2 h to perform gas-phase fluorination treatment. During the treatment, F2 reacts with the surface of silicon suboxide to form an inorganic fluoride layer mainly composed of LiF (usually, direct fluorination produces Si-F and LiF).
[0095] Step 4: Stop the fluorine gas supply, allow the powder to cool naturally to room temperature under an argon atmosphere, remove the powder, and store it in a dry atmosphere to obtain silica suboxide powder with a LiF inorganic layer on the surface.
[0096] Comparative Example 6
[0097] Compared with Example 1, this comparative example does not have step 5, that is, after forming a fluorinated organic control layer on the surface of the hydrogen-rich organic-inorganic interpenetrating soft phase layer in step 4, the solid-liquid separation is performed directly, followed by washing and curing, and the outermost fluorinated organic control layer is not formed.
[0098] Comparative Example 7
[0099] Compared with Example 1, in this comparative example, step 5 uses perfluoropolyether physical adsorption coating and does not add fluorinated organic precursors with reactive end groups.
[0100] Comparative Example 8
[0101] This comparative example only uses an aminosilane coupling agent for monolayer treatment, without a gradient structure. Specific preparation methods include:
[0102] Step 1: Place the silica powder (average particle size D50 of 5.0 μm, purity ≥99.5%) in a vacuum dryer at 120℃ for 8 h.
[0103] Step 2: Prepare an ethanol / water solution (ethanol:water = 9:1, volume ratio) of aminosilane coupling agent (γ-aminopropyltriethoxysilane, KH-550), with a KH-550 concentration of 2 wt%. Adjust the pH to 4.5 with glacial acetic acid.
[0104] Step 3: Add the dried silica powder to the above solution at a powder mass to solution volume ratio of 1:10 (g / mL) and stir the mixture at room temperature for 2 h.
[0105] Step 4: Solid-liquid separation, washing three times with anhydrous ethanol, and drying at 110℃ for 2 h to obtain silica powder with a surface grafted aminosilane monolayer. This treatment did not construct a multilayer gradient structure.
[0106] Comparative Example 9
[0107] Compared with Example 2, the curing stage of this comparative example uses pure water vapor treatment without alcohol vapor, while the rest is the same as Example 2.
[0108] The powders prepared in Examples 1-9 and Comparative Examples 1-9 were used as negative electrode materials and assembled into batteries for performance testing. Lithium-ion battery assembly: First, the prepared powder, conductive carbon black (Super P), and binder (PAA / CMC / SBR) were mixed at a mass ratio of 8:1:1. A slurry was prepared using water as a solvent and uniformly coated onto copper foil, controlling the negative electrode surface loading to be 2.0 mg / cm². 2 ~2.5 mg / cm 2 After drying, using lithium metal sheets as the counter electrode and Celgard 2500 as the separator, an electrolyte consisting of 1.0 mol / L LiPF6 dissolved in EC / DMC / EMC (volume ratio 1:1:1) and with 5 wt% FEC additive was injected to assemble CR2032 coin cells. The battery test voltage range was 0.005 V~1.5 V (vs. Li / Li⁺). The charge / discharge regime was as follows: the first cycle was activated at a current density of 0.05C for 3 cycles, followed by a current density of 0.2C. The test was conducted at a temperature of 25±2℃, and the results are shown in the table below.
[0109]
[0110] As can be seen from the table, compared with Example 1, Example 9 uses a two-step curing process to achieve more thorough interlocking at the molecular level and better gradient synergy, resulting in higher battery capacity retention, first coulombic efficiency and first discharge capacity.
[0111] Comparative Example 1 uses only non-fluorinated silane (TEOS) to construct a single silicon-oxygen layer, without an intermediate soft phase layer, without an outer fluorinated organic layer, without fluorine or gradient, the pure silicon-oxygen layer is rigid insulation, without flexible buffer leading to cyclic cracking, without fluorine passivation leading to persistent interfacial side reactions, the 200-cycle retention rate is only 72.3%, ICE 78.4%, and the specific capacity comparison with Example 1 after 200 cycles is shown in the figure. Figure 2 As shown, the composite powder prepared by the method of the present invention has higher capacity retention and ICE (first coulombic efficiency).
[0112] Comparative Example 2 consists of only a single layer of fluorinated silane, lacking an inner-outer layer gradient structure and a gradient modulus transition. Volume expansion leads to overall cracking of the coating layer, resulting in reduced capacity retention and ICE compared to the battery prepared in this invention. Comparative Example 3 lacks an intermediate soft phase layer, exhibiting inner-outer layer modulus mismatch. Stress concentration at the hard-soft interface triggers delamination, leading to reduced capacity retention and ICE compared to the composite material prepared in Example 1 of this invention.
[0113] Comparative Example 4, a PVDF physical blend without chemical anchoring, experienced interfacial slip failure within a few cycles, resulting in low capacity retention and low ICE. Comparative Example 5, a pure inorganic LiF coating, exhibited high surface rigidity and severe agglomeration in aqueous slurry, leading to uneven electrode distribution and cycle failure, resulting in a capacity retention of 64.5% and the lowest ICE of 73.2%. Comparative Example 6, lacking an outer fluorinated organic control layer, maintained continuous electrolyte contact with the active surface, failing to suppress side reactions, achieving a capacity retention of 79.6% and an ICE of 82.3%. Compared to the powder material with a fluorinated organic control layer in Example 1 of this invention, both capacity retention and ICE were significantly lower. Comparative Example 7, using perfluoropolyether physical adsorption without reactive end groups, desorbed and dissolved in the electrolyte, failing to induce orderly SEI densification, resulting in a capacity retention of 75.4% and an ICE of 79.8%. Compared to Example 1 of this invention, which used a fluorinated organic precursor with reactive end groups, both capacity retention and ICE were reduced. Comparative Example 8 was treated with a conventional silane coupling agent monolayer, but the thickness was too thin and the mechanical constraint was insufficient, resulting in a retention rate of 77.1% and an ICE of 81.2%.
[0114] Compared with Example 2, Comparative Example 9 did not use water / alcohol vapor for curing treatment, resulting in slightly poorer inorganic network densification, and reduced retention rate and ICE.
[0115] Although the invention has been described above in conjunction with exemplary embodiments, those skilled in the art will understand that various modifications and changes can be made to the exemplary embodiments of the invention without departing from the spirit and scope defined by the claims.
Claims
1. A method for preparing silica-suboxide composite powder, characterized in that, Includes the following steps: The first silicon source and the second silicon source are mixed in an organic solvent, and the degree of hydrolysis is controlled by adjusting the amount of water added and the temperature to obtain an active precursor sol. The first silicon source is a fluorinated silane or a fluorinated siloxane oligomer, and the second silicon source is a non-fluorinated silane or a silicate ester. The silica powder is mixed with the active precursor sol to form a silicon-oxygen inorganic anchoring layer on the surface of the silica powder. An activator containing a polar hydrogen donor functional group is added, and a hydrogen-rich organic-inorganic interpenetrating soft phase layer is formed on the surface of the silicon-oxygen inorganic anchoring layer through hydrogen bonding and coordination. By adding fluorinated organic precursors and crosslinking aids, a fluorinated organic regulatory layer is formed on the surface of a hydrogen-bonded organic-inorganic interpenetrating soft phase layer. Solid-liquid separation, washing, and curing processes yield a silica-suboxide composite powder with a gradient fluorine-containing hybrid precursor layer on its surface.
2. The method for preparing silica-suboxide composite powder according to claim 1, characterized in that, The active precursor sol is an active precursor sol with 30%~70% unhydrolyzed alkoxy groups.
3. The method for preparing silica-suboxide composite powder according to claim 1 or 2, characterized in that, Adjusting the amount of water added and controlling the temperature to control the degree of hydrolysis includes controlling the molar ratio of water added to the total of the first and second silicon sources to (0.1~10):1, and the temperature to be 0~60℃, wherein the molar ratio of the first silicon source to the second silicon source is (0.05~20):
1.
4. The method for preparing silica-suboxide composite powder according to claim 1 or 2, characterized in that, The activator is a polyphenol or polyamine compound, selected from one or more of tannic acid, gallic acid, dopamine hydrochloride, catechol, and polyethyleneimine; the fluorinated organic precursor contains reactive end groups and is selected from one or more of fluorinated polyurethane, fluorinated polyimide, fluorinated acrylate polymer, and fluorinated oligomer; the crosslinking aid is selected from one or more of polyisocyanate blocking agents, dialdehyde compounds, and hydrolyzable silane coupling agents.
5. The method for preparing silica-suboxide composite powder according to claim 1 or 2, characterized in that, The fluorinated organic control layer is selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride copolymer, fluorinated acrylate polymer, fluorinated polyimide, fluorinated rubber, fluorinated surfactant and fluorinated oligomer.
6. The method for preparing silica-suboxide composite powder according to claim 1 or 2, characterized in that, The curing process involves placing the washed material in a mixed atmosphere of water vapor and alcohol vapor and performing steam-induced curing at 50°C to 150°C.
7. The method for preparing silica-suboxide composite powder according to claim 1 or 2, characterized in that, The curing process involves placing the washed material in an atmosphere containing alcohol vapor and treating it at 60℃~100℃ for 0.5h~2h, and then placing it in a mixed atmosphere containing water vapor and alcohol vapor and treating it at 50℃~150℃ for 1h~4h.
8. A silica-suboxide composite powder, characterized in that, The silicon suboxide composite powder is prepared by any one of claims 1 to 7, wherein the thickness of the silicon-oxygen inorganic anchoring layer is 2 nm to 10 nm, the thickness of the hydrogen-rich organic-inorganic interpenetrating soft phase layer is 1 nm to 5 nm, and the thickness of the fluorine-containing organic regulating layer is 5 nm to 20 nm.
9. A lithium battery negative electrode, characterized in that, It contains the silica-suboxide composite powder as described in claim 8.
10. A lithium battery, characterized in that, It includes the lithium battery negative electrode as described in claim 9.
